Proteinase-activated receptors in fibroproliferative lung disease. Issue 2 (1st November 2013) - José, Ricardo J; Williams, Andrew E; Chambers, Rachel C
Abstract : The coagulation cascade plays a central role in the pathogenesis of fibroproliferative lung diseases such as the acute respiratory distress syndrome (ARDS) and idiopathic pulmonary fibrosis (IPF) through multifaceted effects on haemostasis, inflammation and tissue repair. However, targeting the coagulation cascade using traditional anticoagulant approaches has not resulted in improved outcomes for these patients. The cellular effects of the coagulation cascade are mediated via a family of four proteinase-activated receptors (PAR1–4 ). PARs are G protein-coupled receptors that have a unique method of activation involving proteolytic cleavage. They play key roles in mediating the interplay between coagulation and inflammation and tissue repair and fibrosis. Current evidence suggests a central role for PAR1 and PAR2 in influencing these responses, although data from animal models suggest that their contribution is highly dependent on both the nature of the insult and disease status. Nonetheless, these receptors may represent important targets in conditions associated with uncontrolled coagulation signalling responses including IPF, ARDS, asthma and chronic obstructive pulmonary disease.